2022
DOI: 10.1108/jicv-06-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Intersection control with connected and automated vehicles: a review

Abstract: Purpose This paper aims to review the studies on intersection control with connected and automated vehicles (CAVs). Design/methodology/approach The most seminal and recent research in this area is reviewed. This study specifically focuses on two categories: CAV trajectory planning and joint intersection and CAV control. Findings It is found that there is a lack of widely recognized benchmarks in this area, which hinders the validation and demonstration of new studies. Originality/value In this review, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…With the aim to assigning a central role of public transit [7], policy makers and operators should provide a reliable and accessible service in their cities [11]. To achieve the same target, innovative mobility solutions, such as connected autonomous vehicles [2,3], could contribute to automatically prioritizing public transport means on the road. Furthermore, the results confirmed that escooter sharing could be an effective mobility option that can complement public transport as a last-mile solution [40], thus fostering its adoption within an MaaS ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim to assigning a central role of public transit [7], policy makers and operators should provide a reliable and accessible service in their cities [11]. To achieve the same target, innovative mobility solutions, such as connected autonomous vehicles [2,3], could contribute to automatically prioritizing public transport means on the road. Furthermore, the results confirmed that escooter sharing could be an effective mobility option that can complement public transport as a last-mile solution [40], thus fostering its adoption within an MaaS ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread diffusion of digital technologies and recent shifts toward serviceoriented approaches, as opposed to asset-oriented approaches, have prompted deep impacts in several sectors, including mobility [1][2][3]. From this perspective, Mobility as a Service (MaaS) is considered as an innovative ecosystem that will lead to disruptive changes in the concept of mobility [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [13] proposed a real-time predictive distributed CACC control framework that addresses time delays, actuator lag, and utilizes intent-sharingbased distributed computing to improve string stability under various traffic dynamics by formulating a Kalman-filter-based real-time current driving state prediction model, thus solving the problem using a sequential Kalman filter update process and implementing a real-time distributed MPC-based CACC controller with delay-compensated predicted initial conditions. Existing research indicates that, when compared with noncooperativebehavior-based models, cooperative-behavior-based CACC methods can provide smoother acceleration and deceleration behaviors, thereby ultimately enhancing the stability and safety of CAV platoon systems [14].…”
Section: Introductionmentioning
confidence: 99%
“…Intersections are the bottleneck that affects the traffic efficiency of urban road networks (Wu and Qu, 2022;Yu et al, 2021). Under saturated flow conditions, congestion and queue overflow are more likely to occur, resulting in greater loss of traffic efficiency (Vahidi and Sciarretta, 2018).…”
Section: Introductionmentioning
confidence: 99%